Application of New Energy Technologies in Aero Engines and Gas Turbines - Lv, Xinxiong (Scientific Journal of Technology, 2026)
The intensification of global climate change and environmental pollution has made achieving carbon peaking and carbon neutrality a core strategy for global development. With the continuous advancement of new energy technologies, the utilization of clean energy sources such as wind, solar, and hydrogen has brought profound transformations to the traditional energy structure. In this context, the fields of aero engines and gas turbines are also facing both pressure and opportunities for low-carbon transition. This paper analyzes new energy power generation technologies under the “dual carbon” strategy, and, in conjunction with the working principles and development trends of aero engines and gas turbines, explores the application prospects and challenges of these technologies in the aviation and energy sectors. It further proposes a technological integration pathway for low-carbon and high-efficiency power systems. The results indicate that the integration of new energy generation technologies with aero engines and gas turbines provides a feasible technical route for advancing the green energy transition; however, numerous technical challenges remain to be addressed in practical applications.